2007
DOI: 10.1002/j.0022-0337.2007.71.5.tb04325.x
|View full text |Cite
|
Sign up to set email alerts
|

Medical Profile of a Dental School Patient Population

Abstract: Advances in health care and pharmacotherapeutics have led to a growing aging population living with complex medical conditions. These changes are apparent in patients presenting for treatment at dental schools. This study assessed the medical profile of patients seeking treatment at the School of Dental Medicine, State University of New York at Buffalo. Medical records of 1,041 consecutive patients who presented for comprehensive dental care at the school were retrospectively reviewed. The demographic data, me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
37
2
9

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(57 citation statements)
references
References 14 publications
9
37
2
9
Order By: Relevance
“…Cardiovascular disease (37.9%), allergy (32.3%), mental health disorders (29.4%) musculoskeletal (23.0%) endocrine (22.4%) and respiratory disease (17.8%) constituted the most common conditions reported with the pattern of medication usage paralleling the diseases reported. This is in keeping with other studies [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] and also re ects the most common chronic diseases in Australia [27]. Each of those conditions and associated medication use can not only contribute to the presentation of numerous intraoral pathosis but also affect the safe delivery of dental treatment.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Cardiovascular disease (37.9%), allergy (32.3%), mental health disorders (29.4%) musculoskeletal (23.0%) endocrine (22.4%) and respiratory disease (17.8%) constituted the most common conditions reported with the pattern of medication usage paralleling the diseases reported. This is in keeping with other studies [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] and also re ects the most common chronic diseases in Australia [27]. Each of those conditions and associated medication use can not only contribute to the presentation of numerous intraoral pathosis but also affect the safe delivery of dental treatment.…”
Section: Discussionsupporting
confidence: 88%
“…Of note, 17% of study participants reported taking anticoagulants, with men signi cantly more likely to be affected (p=0.0033; odds ratio [95%CI]: 0.59 [0.41 -0.84]). Although this gure is signi cantly higher than is reported in the literature [6,7], it is not unexpected give the high prevalence of cardiovascular and nervous system disease in the population studied. Our study participants were also speci cally questioned about bleeding during medical history taking and were therefore potentially more likely to recall taking such medication.…”
Section: Discussioncontrasting
confidence: 64%
“…Cardiovascular disease (37.9%), allergy (32.3%), mental health disorders (29.4%) musculoskeletal (23.0%) endocrine (22.4%) and respiratory disease (17.8%) constituted the most common conditions reported with the pattern of medication usage paralleling the diseases reported. This is in keeping with other studies [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] and also re ects the most common chronic diseases in Australia [25]. Each of those conditions and associated medication use can not only contribute to the presentation of numerous intraoral pathosis but also affect the safe delivery of dental treatment.…”
Section: Discussionsupporting
confidence: 88%
“…The evaluation of the medical profile of children consulting at university hospitals is of great importance at the global level. In fact, several studies have been conducted in this direction, most of which are focusing on the medical profile of adult patients [4,5,[7][8][9][10]. However, few studies have addressed the subject of the medical profile of children consulting for dental care [1,11,12].…”
Section: Introductionmentioning
confidence: 99%